A critical analysis of the legal framework regulating indigenous and community conserved areas in Namibia - Meyer, Adri (Institute of Marine and Environmental Law, 2015)
Protected areas, formally established by governments, are one the key methods of preventing natural resource degradation by excluding humans from accessing certain sensitive areas, or by regulating the activities within these areas. Protected areas are viewed as essential for conserving the biodiversity on which the human race depends. However, the "fine and fences" preservationist approach to conservation has proved ineffective and it has been determined that often degradation occurs due to a lack of synchronisation between communities and their environments. This has led to the development and adoption of the community-based natural resource management (CBNRM) approach to conservation. The main principle of CBNRM is that traditional knowledge be applied and user-rights be legally devolved to indigenous communities in order to sustainably manage and conserve natural resources. Indigenous and community conserved areas (ICCAs) can be viewed as a tool to promote CBNRM. Communities voluntarily establish ICCAs and if the ICCA is recognised in legislation, they are then awarded a bundle of rights to manage and use resources while simultaneously implementing conservation activities. Certain key prerequisites are required in legislation and policy to promote effective and equitable ICCAs, including rights to land tenure, management and access, use and benefits to natural resources on communal land. Namibia has adopted a novel approach to CBNRM by the establishment of three types of ICCAs – conservancies, community forests and wildlife concessions. Different bundles of rights are awarded to communities who establish these ICCAs. Namibia has various policies and acts influencing the awarding of rights. These include the constitutional rights and freedoms, the amended Nature Conservation Ordinance, the Communal Lands Reform Act, the Traditional Authorities Act, the Forest Act and a variety of policies. Conservancies and community forests have benefit-sharing plans in place and cash revenues and non-economic benefits are shared equitably amongst members, therefore empowering the community as a whole. Communities adjacent to or within protected areas, to which concessions are granted, are able to enjoy access to resources within the protected area. One major shortcoming of Namibia's CBNRM legislation is the lack of secure land tenure in terms of property rights awarded to ICCAs. Without property rights, conservancies are not able to exclude outsiders from the communal state-owned land on which they are situated which leads to open access issues and lack of incentive to implement efforts to conserve natural resources. Although issues are still present, the Namibian legislature contains the basics of a successful national CBNRM movement.